An investigation to find the correlation between lupus anticoagulant and coagulation abnormalities in COVID-19 patients; a narrative review - Amir Aria; Ahmadreza Maghsoudi; Fatemeh Shafiee; Mahnaz Momenzadeh (Society of Diabetic Nephropathy Prevention, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of coronavirus disease 2019 (COVID-19) which is associated with nonspecific respiratory syndromes, varying from mild symptoms of upper airway to required mechanical ventilation hypoxemia. A unique feature of this disease is COVID-19-associated coagulopathy (CAC) that linked with disease severity and hospital mortality. These patients have a profound hypercoagulable state and in patients with severe type arterial and venous thrombotic events are frequent. Abnormal coagulation parameters such as activated partial thromboplastin time (aPTT) were observed in patients with COVID-19. Regarding the above finding it could be considered as a reason to avoid anticoagulation at the both doses of therapeutic and prophylactic. A prolonged aPTT may indicate a coagulation factor deficiency or inhibitor of coagulation, which can be specific (antibody to factor VIII) or nonspecific (lupus anticoagulant, LA). LA can affect laboratory tests of blood coagulation, but is not usually associated with bleeding; however, it can be associated with thrombotic risk as a part of the antiphospholipid syndrome. In a phospholipid concentration-dependent manner LA recognizes a type of antiphospholipid antibodies (aPLs) that prolong clotting tests. In patients with antiphospholipid syndrome (APS) LA is considered as one of the laboratory criteria representing a significant risk factor of both thrombosis and pregnancy morbidity. Similarities between some of the pathophysiological features of COVID-19 and APS has been focused in several reports particularly in the most severe form, catastrophic APS. This study aimed to evaluate the effect of LA on the incidence of thrombophilia in patients with COVID-19, as well as its impact on the inflammation and finally the mortality final rate.